Clinical utility of next-generation sequencing-based ctDNA testing for common and novel ALK fusions. (September 2021) - Mondaca, Sebastian; Lebow, Emily S.; Namakydoust, Azadeh; Razavi, Pedram; Reis-Filho, Jorge S.; Shen, Ronglai; Offin, Michael; Tu, Hai-Yan; Murciano-Goroff, Yonina; Xu, Chongrui; Makhnin, Alex; Martinez, Andres; et al.
Highlights: Liquid biopsy for plasma ctDNA NGS is capable of partner agnostic detection of ALK fusions. A subset of patients can be matched to ALK-directed therapy based on plasma ctDNA testing. PON1, a novel ALK fusion partner, was detected in plasma in a lung cancer patient. Abstract: Objectives: Liquid biopsy for plasma circulating tumor DNA (ctDNA) next-generation sequencing (NGS) can detect ALK fusions, though data on clinical utility of this technology in the real world is limited. Materials and Methods: Patients with lung cancer without known oncogenic drivers or who had acquired resistance to therapy (n = 736) underwent prospective plasma ctDNA NGS. A subset of this cohort ( n  = 497) also had tissue NGS. We evaluated ALK fusion detection, turnaround time (TAT), plasma and tissue concordance, matching to therapy, and treatment response. Results: ctDNA identified an ALK fusion in 21 patients (3%) with a variety of breakpoints and fusion partners, including EML4, CLTC, and PON1, a novel ALK fusion partner. TAT for ctDNA NGS was shorter than tissue NGS (10 vs. 20 days; p < 0.001). Among ALK fusions identified by ctDNA, 93% (13/14, 95% CI 66%–99%) were concordant with tissue evaluation. Among ALK fusions detected by tissue NGS, 54% (13/24, 95% CI 33%–74%) were concordant with plasma ctDNA. ctDNA matched patients to ALK-directed therapy with subsequent clinical response, including four patients matched on the basis of ctDNA results alone due to inadequate or delayed tissue testing. Serial ctDNA analysis detected MET amplification ( n  = 2) and ALK G1202R mutation ( n  = 2) as mechanisms of acquired resistance to ALK-directed therapy. Conclusion: Our findings support a complementary role for ctDNA in detection of ALK fusions and other alterations at diagnosis and therapeutic resistance settings.